Improving the Delivery of Drugs and Nucleic Acids to T Cells Using Nanotechnology. Issue 8 (22nd June 2021) - Lou, Jenny; Heater, Alexandra; Zheng, Gang
Abstract : T cells play several roles in antitumor immunity, including mediating cytotoxicity, generating immune memory, and promoting humoral immunity. Given these critical roles, T cells are the therapeutic target of immunotherapies that have achieved clinical success, notably immune checkpoint inhibitors and chimeric antigen receptor T‐cell therapy. However, a fraction of patients benefits from these treatments due to intolerable toxicities and limited efficacy. These issues stem in part from inefficient and nonselective drug delivery to T cells. Nanotechnology may help resolve these delivery issues, as nanoparticles can serve as modular drug delivery vehicles with targeting abilities that can be applied for ex vivo and in vivo delivery. Herein, applications of nanotechnology in improving extracellular delivery of cytokines and small molecule drugs and intracellular delivery of siRNA to T cells are described. An overview of nanoparticle‐mediated delivery of nucleic acids for chimeric antigen receptor T‐cell therapy and CRISPR/Cas9 genome editing is provided. Finally, an outlook on the challenges and opportunities for the advancement of nanoparticle‐mediated drug delivery to T cells is shared. Abstract : As key mediators of antitumor immunity, T cells are excellent therapeutic targets for interventions. Herein, it is described how nanotechnology can improve the delivery of cytokines, small molecule drugs, siRNA, and mRNA to T cells. The authors highlight CAR T‐cell therapy and CRISPR/Cas9 genome editing.